Analisis Siklus Kebijakan Sekolah Ramah Anak di MTSN 6 Sleman - Diah Rusmala Dewi (MANAZHIM, 2020)
This study aims to describe the cycle of child-friendly school policies in MTsN 6 Sleman. This type of research is descriptive qualitative. Data collection techniques using interviews, observation and documentation. Source triangulation is carried out to obtain data validity. Data analysis techniques include data collection, data reduction, data presentation, and verification or conclusion drawing. The results of the study include: the child-friendly school policy cycle in MTsN 6 Sleman including after passing through the stages of agenda preparation, policy formulation, and policy adoption, four policy packages were born to strengthen the Child Friendly School Policy (SRA) so that it can be implemented in the regions, one of which is at MTsN 6 Sleman involving all parties involved. The results of the study include: the child-friendly school policy cycle in MTsN 6 Sleman including after passing through the stages of agenda preparation, policy formulation, and policy adoption, four policy packages were born to strengthen the Child Friendly School Policy (SRA) so that it can be implemented in the regions, one of which is at MTsN 6 Sleman involving all parties involved. Then, the stages of implementing child-friendly school policies in MTsN 6 Sleman, namely: Bureaucratic Structure, Communication of Human Resources, infrastructure, and finance, and Disposition. The learning model used in MTsN 6 Sleman is sufficient to apply the principles of child-friendly schools, namely provision, protection, and participation. Supporting factors are human resources, infrastructure, and financial while the inhibiting factor is the lack of maximum infrastructure and financial resources in creating facilities that are friendly for children with disabilities. Monitoring and evaluation of the implementation of friendly school programs in MTsN 6 Sleman is carried out by the SRA Development Team and involves the KLA task force and other agencies.